Diagnostics and treatment of chronic urticaria in the family doctor’s office - Malita, Agnieszka; Fabian-Danielewska, Anna (Journal of Education, Health and Sport, 2018)
Urticaria is classified as a sever, chronic, allergic disease with a phase of remission and exacerbation. The basic dermatitis is wheal. The classification of urticaria is based on the causing factor and the duration of symptoms. The UAS-7 score is used to assess the severity of symptoms. It is as a simple tool used by patients and physicians. In the diagnosis of urticaria, the most important element is a meticulous interview, which may indicate the cause of the disease but usually it remains unknown. Treatment is based on H1 receptor antagonists usually in high dosage - even 4 time higher than the standard one.